2015
DOI: 10.5194/piahs-367-312-2015
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the flux and fate of the Mississippi and Yangtze river sediments

Abstract: Large rivers play a key role in delivering water and sediment into the global oceans. Large-river deltas and associated coastlines are important interfaces for material fluxes that have a global impact on marine processes. In this study, we compare water and sediment discharge from Mississippi and Yangtze rivers by assessing: (1) temporal variation under varying climatic and anthropogenic impacts, (2) delta response of the declining sediment discharge, and (3) deltaic lobe switching and Holocene sediment dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The obtained results are in line with the literature where the impact on the hydrological regimes of TGD construction, impoundment, and operation has been extensively studied [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], altering the hydrodynamic conditions, increasing the sediments deposition, and thus reshaping the riverscape. In particular, Zhou et al [48], observed a significant reduction on the incoming sediment with the flushing ratio of sediment being only 24.2% from June 2003 to December 2015 suggesting that a large amount of sediment has been retained by TGD after water impoundment.…”
Section: Discussionsupporting
confidence: 90%
“…The obtained results are in line with the literature where the impact on the hydrological regimes of TGD construction, impoundment, and operation has been extensively studied [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], altering the hydrodynamic conditions, increasing the sediments deposition, and thus reshaping the riverscape. In particular, Zhou et al [48], observed a significant reduction on the incoming sediment with the flushing ratio of sediment being only 24.2% from June 2003 to December 2015 suggesting that a large amount of sediment has been retained by TGD after water impoundment.…”
Section: Discussionsupporting
confidence: 90%
“…Several hundreds of thousands of dams have been built in global river basins for generating hydropower, diverting water, and mitigating flood over the past century. For instance, more than 50,000 dams have been built in the Mississippi River basin alone and a similar number of dams have been built on the Yangtze River basin as well (Xu & Yang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous reservoir sedimentation studies have mainly focused on exorheic rivers such as the Yangtze (Yang et al 2014 . Luo et al 2012 , Yang et al 2018b ), Yellow (Walling 2006 ; Wang et al 2007 ), Colorado (Vörösmarty et al 2003 ), and Mississippi rivers (Meade and Moody 2010 ; Xu and Yang 2015 ). For endorheic rivers originating from the Tibetan Plateau in China where the river gradient is greater, the water depth is shallower, and the flow velocity is fast, which makes the sediment transport characteristics of the river even more complicated under the condition of cascade construction; the influence of high-altitude endorheic river dam construction on the sediment transport process has received much less attention.…”
Section: Introductionmentioning
confidence: 99%